Pemberdayaan Perempuan Melalui Pelatihan Kewirausahaan di Desa Karangpatihan Ponorogo - Safitri, Anisa; Latifah, Khairi Fitriana (STAI Terpadu Yogyakarta, 2024)
The aim of this community service program is to empower women in Karangpatihan Village, Ponorogo, through entrepreneurship training. This research aims to identify the factors influencing the success of women's empowerment, the impact of entrepreneurship training on family economic improvement, and the challenges faced by women in implementing the results of the training. The method used in this community service is a skill-based training approach implemented through workshops and direct simulations. The participants are women in Karangpatihan Village who either own a business or are interested in starting one. The results of the community service indicate that the success factors include access to resources, family support, as well as personal motivation and ability. The entrepreneurship training had a positive impact on the economic improvement of the participants' families, although challenges such as limited time, capital, and social-cultural barriers were still encountered by some participants. This program successfully improved entrepreneurial skills and directly affected the participants' family welfare. Therefore, it is recommended to strengthen continuous mentoring, improve access to capital, and enhance social support to expand the impact of this program.